The validation of new vibration measurement to estimate sound propagation in buildings: study cases - Gervásio, Nuno (2019)
The main objective of the present work is the prediction of the paths of noise propagation between interior spaces of buildings, generated by internal sound sources, using an alternative experimental methodology. With this methodology, it is intended to obtain more rigorous results, with a certain solution of sound insulation, in relation to the contribution of each one of the sound paths, in comparison to the direct sound measurement. The proposed methodology is based on the use of a vibration measurement of the elements separating internal spaces (floor, ceiling, walls) to estimate the sound field in the receiver space, together with the sound measurements to estimate the sound field in the emitter space. The proposed method is validated through tests carried out on existing buildings in comparison with the results obtained from the classical measurement of acoustic insulation. The study cases were carried out for different types of constructive solutions and different types of buildings. The analysis of the study cases exposed the existence of an acceptable similarity between the results obtained through the two methodologies.